Clinical study of prolonged jaundice in breast- and bottle-fed babies. Issue 6 (June 1978) - Winfield, C R; MacFaul, R
Abstract : A study of 893 births was undertaken to determine the incidence of prolonged neonatal jaundice. 55% of these babies were breast feeding on discharge from the maternity hospital. Jaundice lasting for 3 weeks or more was found in 12 breast-fed term babies (2-4% of all breast-fed babies), and in no bottle-fed infant. 3 of the jaundiced babies gained weight poorly in the first 3 weeks of life, but after that age failure to thrive was not associated with the prolonged jaundice. The hyperbilirubinaemia, which persisted in 11 infants from between 21 to 80 days (mean 39 days), was due to elevations in both conjugated and unconjugated fractions.